2023
DOI: 10.3390/ijms241512032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lipid Metabolism on Macrophage Polarization: Implications for Inflammation and Tumor Immunity

Abstract: Macrophage polarization is influenced by lipids, which also exert significant control over macrophage functions. Lipids and their metabolites are players in intricate signaling pathways that modulate macrophages’ responses to pathogens, phagocytosis, ferroptosis, and inflammation. This review focuses on lipid metabolism and macrophage functions and addresses potential molecular targets for the treatment of macrophage-related diseases. While lipogenesis is crucial for lipid accumulation and phagocytosis in M1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…20 In recent years, researchers have begun to focus on AA metabolism in tumor biological functions and immune regulation. 21,22 In this study, we established a targeted metabolomics method for detecting AA metabolites using LC-MS/MS. We investigated the AA metabolite profiles of serum and tissue samples from CRC patients and healthy individuals, finding that the PGE2 biosynthetic pathway was upregulated in CRC and was positively associated with macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…20 In recent years, researchers have begun to focus on AA metabolism in tumor biological functions and immune regulation. 21,22 In this study, we established a targeted metabolomics method for detecting AA metabolites using LC-MS/MS. We investigated the AA metabolite profiles of serum and tissue samples from CRC patients and healthy individuals, finding that the PGE2 biosynthetic pathway was upregulated in CRC and was positively associated with macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic process that facilitates cFAS impact on foam cell formation is currently unknown. However, prior work demonstrates that endogenous FAS in macrophages is essential for the retention of plasma membrane cholesterol, cellular adhesion, and migration, as well as recruitment into adipose tissue that facilitates chronic tissue in ammation induced by nutrient dense diets 50,[56][57][58][59][60] . In our study, we similarly observed that pharmacological inhibition of FAS with PTM in mice maintained on 42% high-fat diet dramatically reduced macrophage in ltration in both hepatic and white adipose tissue (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolytic metabolic pathway regulates the immune system [ 66 ]. Similar to lipid metabolism, glycolysis can adjust the macrophage activation state and cell function by regulating polarization [ 67 , 68 ]. However, the association between glycolysis and IgAN remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%